(3Yde GdOjfGJhdhLj (BTMs (3dZI GdHQGfcG ddJhGUd Hjf Gdcaja hGdCUes - (3UHQj, Cejf eMehOs ((3GdefUhQI, eUQs (3GdecJHI GdYUQjIs, 2011)
(3djS GdCeQ eYbOkG Ch CffG fJcde Yf GdfXQjI GdfSHjI, Hd GdCeQ CZQH ef Pdc EffG fMf GdHTQ fYjT efP CdGa GdSfjf hSW Gdchf GdeGOj hfSJYed chfkG BNQ dhdGg deG cGfJ gfGc MVGQGJ hYdhe heYGQa, Efg chf BNQ OGNd cd TNU efG aj JacjQg haj JhGUdg eY GdfGS, Efg Gdchf GdeejR dfG fMf GdHTQ, gPG Gdchf jHOC ef fXQI CYjffG Edi cdeGJ CahGgfG Edi SdhcjGJfG aMQcGJfG aj GdCQV habkG deG facQ ajg heG facQ ajg jCJj habkG deG fJdbGg ef eYdheGJ heG feQ Hg ef NHQGJ hJLGQH,s
12
Keywords: (3GdEOQGc GdPgfjs; (3GdHOjgjIs; (3GdeYQaIs